أثر توظيف نصوص من نهج البلاغة للإمام علي (عليه السلام) في تحصيل طالبات الصف الخامس العلمي في مادة قواعد اللغة العربية - عدنان حسين العنبكي, قحطان (Journal of College of Education, 2020)
The aim of the research is to identify ( The effect of using texts from the rhetoric approach of Imam Ali ( peace upon him ) in the achievement of the fifth female students in Arabic grammar ) .                         The researcher formulated the null hypothesis .The research sample consisted of (64) students, The section (A) has been selected which have (32) students to represent the experimental group, and section (B) that have (32) students to represent the control group, The researcher formulated (80) behavioral goals in its final form  after presenting them to the experts and specialists. He prepared the teaching plans for the two research groups . The researcher matched between the two categories in the changeable of ( the academic achievement, students age, the parents academic achievement, and the usage of the appropriate statistical principles ) The results evidenced that ( there is a different at the significance level (0,05) for the experimental group ) and thus dismiss the null hypothesis and accept the alternative . In view of the results, the researcher attained a set of conclusions, recommendations and suggestions .